2006
DOI: 10.1128/ec.5.3.447-456.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of xyn1 , Encoding Xylanase I, in Hypocrea jecorina

Abstract: Two major xylanases (XYN I and XYN II) of the filamentous fungus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
167
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(189 citation statements)
references
References 55 publications
12
167
2
3
Order By: Relevance
“…The simultaneous presence of D-glucose and xylan leads to a drop of the transcription to the basal level, whereas the induction of the xyn2 transcription by xylobiose is not affected by D-glucose (Würleitner et al 2003). However, the xyn1 transcription which is induced by D-xylose is not affected by the simultaneous presence of Dglucose and D-xylose, whereas D-glucose alone completely represses its expression Rauscher et al 2006). Recently, a general model for the substrate recognition and the induction mechanisms of the major xylanolytic and cellulolytic enzymes of H. jecorina including the general in trans-acting activator Xyr1 (Fig.…”
Section: Functional Domains In a Niger Xlnrmentioning
confidence: 84%
See 2 more Smart Citations
“…The simultaneous presence of D-glucose and xylan leads to a drop of the transcription to the basal level, whereas the induction of the xyn2 transcription by xylobiose is not affected by D-glucose (Würleitner et al 2003). However, the xyn1 transcription which is induced by D-xylose is not affected by the simultaneous presence of Dglucose and D-xylose, whereas D-glucose alone completely represses its expression Rauscher et al 2006). Recently, a general model for the substrate recognition and the induction mechanisms of the major xylanolytic and cellulolytic enzymes of H. jecorina including the general in trans-acting activator Xyr1 (Fig.…”
Section: Functional Domains In a Niger Xlnrmentioning
confidence: 84%
“…The bi-nuclear cluster domain forms the DNAbinding domain and is found in XlnR at the N-terminal part of the protein, formed by amino acids from position 49 till 91. In this region, only two amino acid changes are found compared to the DNA-binding domain of the XlnR orthologue in H. jecorina, Xyr1 (xylanase regulator 1; Stricker et al 2006;Rauscher et al 2006). …”
Section: Functional Domains In a Niger Xlnrmentioning
confidence: 99%
See 1 more Smart Citation
“…171 The promoters of many glucose-repressible target genes have Cre-binding consensus sequences. 172 The Cre1 protein (from the cre1 gene) sequence shows high similarity to other glucose-repressor proteins from filamentous fungi, suggesting a similar regulation and a related role in CCR. Janus et al 171 identified a 114-bp minimal promoter with two Cre1-binding sites, the first minimal regulatory promoter sequence for the b-lactam antibiotic-producing fungus.…”
Section: Carbon Source Regulation Of Secondary Metabolism Biosynthesimentioning
confidence: 96%
“…Expression can also be repressed when those enzymes are not needed. Production of xylanases and other accessory CWDEs is controlled in part by the transcriptional activator Xyr1 in T. reesei and G. zeae, and the orthologous XlnR in F. oxysporum (Brunner et al, 2007;Calero-Nieto et al, 2007, 2008Rauscher et al, 2006;Stricker et al, 2006). Growth media is known to influence microbial enzymatic diversity and activity (Duff et al, 1987).…”
Section: Hydrolytic Activitymentioning
confidence: 99%